2009
DOI: 10.1093/nar/gkp217
|View full text |Cite
|
Sign up to set email alerts
|

Targeted correction of a thalassemia-associated  -globin mutation induced by pseudo-complementary peptide nucleic acids

Abstract: β-Thalassemia is a genetic disorder caused by mutations in the β-globin gene. Triplex-forming oligonucleotides and triplex-forming peptide nucleic acids (PNAs) have been shown to stimulate recombination in mammalian cells via site-specific binding and creation of altered helical structures that provoke DNA repair. However, the use of these molecules for gene targeting requires homopurine tracts to facilitate triple helix formation. Alternatively, to achieve binding to mixed-sequence target sites for the induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…In the last years, different approaches have emerged to correct a point mutation at the DNA level without provoking doublestrand breaks (DSB): chimeric RNA-DNA oligonucleotides, which were first designed by Kmiec's group (Yoon et al, 1996); single-stranded oligonucleotides, studied for the first time in 1988 (Moerschell et al, 1988); bifunctional triplehelix-forming oligonucleotides, formed by two domains, a triplex forming oligonucleotide (TFO) domain and a repair domain (Chan et al, 1999;Culver et al, 1999); and several approaches of peptide nucleic acids (PNA) (Nielsen et al, 1991;Egholm et al, 1993), bis-PNA (Rogers et al, 2002;Chin et al, 2008), tc-PNA (Bentin et al, 2003;Kaihatsu et al, 2003), pc-PNA (Lohse et al, 1999) (Demidov et al, 2002;Lonkar et al, 2009), and more recently PNA-single-stranded oligodeoxynucleotides (ssODNs) (Kayali et al, 2010;NikAhd and Bertoni, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, different approaches have emerged to correct a point mutation at the DNA level without provoking doublestrand breaks (DSB): chimeric RNA-DNA oligonucleotides, which were first designed by Kmiec's group (Yoon et al, 1996); single-stranded oligonucleotides, studied for the first time in 1988 (Moerschell et al, 1988); bifunctional triplehelix-forming oligonucleotides, formed by two domains, a triplex forming oligonucleotide (TFO) domain and a repair domain (Chan et al, 1999;Culver et al, 1999); and several approaches of peptide nucleic acids (PNA) (Nielsen et al, 1991;Egholm et al, 1993), bis-PNA (Rogers et al, 2002;Chin et al, 2008), tc-PNA (Bentin et al, 2003;Kaihatsu et al, 2003), pc-PNA (Lohse et al, 1999) (Demidov et al, 2002;Lonkar et al, 2009), and more recently PNA-single-stranded oligodeoxynucleotides (ssODNs) (Kayali et al, 2010;NikAhd and Bertoni, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In addition, these compounds have been used to inhibit transcription and to stimulate site-directed recombination of a co-transfected donor DNA, resulting in correction of a mutation in the target gene. [9][10][11][12] TFOs have also been used to study mechanisms of DNA damage and repair, recombination and structurally induced genomic instability. Previous studies have demonstrated that triplex formation itself induces mutagenesis and stimulates DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide Previous studies on PNA oligomers in gene correction approaches have focused on DNA helix invading bis-PNAs, 8,9 that form P-loops with an internal PNA-DNA-PNA triplex binding to the target DNA strand, 10 or pseudocomplementary PNAs forming double duplex invasion complexes in which two PNA oligomers each bind one of the target DNA strands. 11 For both types of PNAs a limited but significant augmentation of gene correction rates were observed in cells in culture.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%